A novel in-silico approach to design a multiepitope peptide as a vaccine candidate for Aeromonas hydrophila - Mahdieh SobhZahedi; Mohammad Hossein YektaKooshali (Heliyon)
Introduction: Aeromonas hydrophila is a Gram-negative bacterium with a rod-shaped structure and a member of the Aeromonas genus. It is commonly found in aquatic environments such as freshwater, estuaries, and sewage. Known as an opportunistic pathogen, A. hydrophila can infect both aquatic animals and humans. Understanding this bacteria's virulence factors, pathogenic mechanisms, and epidemiology is crucial due to its clinical significance and potential impact on public health, to develop effective disease management and prevention strategies. A. hydrophila has developed resistance to numerous antibiotics, making it challenging to combat, so vaccination can be a hopeful strategy for targeting this bacterium. Despite the development of multiple vaccine candidates for this bacterium, no commercially available vaccine has demonstrated high effectiveness. This study aimed to design a vaccine candidate that has the potential to effectively combat A. hydrophila infections, by using an informatics server. Methods: Servers and bioinformatics tools were used to find and evaluate vaccine candidates. The bacterial genome was extracted and open reading frames were identified. The toxicity, allergenicity, immunogenicity, and homology of ORFs were investigated and non-toxic, non-allergenic with highly immunogenic were selected as a candidate for vaccine design. Next, epitopes were predicted and combined with adjuvants, linkers, and his-tag to create the vaccine candidate. Afterward, a thorough assessment of the vaccine was carried out. Results: After the investigations, an extracellular protein with access number WP_045528985.1 was selected as a vaccine candidate. Combining a total of 15 epitopes for B cells and T cells, the vaccine candidate was completed. The analysis showed that the structure of the vaccine is non-toxic, non-allergenic, and has a favorable immunogenicity score of 0.8573. Additionally, the designed vaccine passed all virtual tests, including analysis of physical and chemical characteristics, and valuations of secondary and tertiary structure. Conclusion: According to the results, this multiepitope peptide can be used as a promising vaccine candidate which warrants further development. Furthermore, further investigation is required to examine the functional characteristics, in vitro and in vivo experiments, potential applications, and animal model studies to confirm the safety, effectiveness, and long-term impacts of the vaccine formulation.